Solitary rib Metastasis from primary nasopharyngeal carcinoma: a rare clinical presentation - Abrar, Sehrish; Qureshi, Bilal Mazhar; Ali, Nasir; Hafiz, Asim; Khan, Agha Mohammad Hammad; Abbasi, Ahmed Nadeem (Journal of the Pakistan Medical Association, 2022)
We report a case of a middle age male who presented to our tertiary care university hospital with the complaints of nasal obstruction and decrease hearing. The CT scan of head and neck exhibited a mass in nasopharynx and enlarged bilateral cervical lymph nodes. Biopsy from nasopharynx confirmed the lesion as poorly differentiated non-keratinizing squamous cell carcinoma and staged as cT2N2M0. He received neoadjuvant chemotherapy. Subsequently, he underwent chemo radiation therapy. He represented with left chest wall pain. Imaging confirmed isolated lesion on left sided 6th rib. Rib lesion was resected followed by radiation therapy to surgical bed and systemic treatment. The patient remained disease free for 4.5 years. Later, his disease relapsed, and he died of systemic disease progression. –Continue